Sosialisasi gemar menabung sejak dini - Nurmiati Irvan; Fina Diana; Ilham Ilham; Irwan Syarif; Sri Nurindasari (Universitas Patria Artha, 2022)
Saving should have been introduced from an early age both by the school and in the family environment, although there has not been a special curriculum presented at the elementary school level regarding this, even though it is important to introduce it to early childhood children because early age is the golden age in growing everything. the potential that exists in children, in times like these children will record every information they get to later be applied in their daily lives. The problems faced by partners in community service activities include the lack of understanding of students about saving activities and the importance of saving from an early age and the perception of students who think that saving activities are only for people who are adults and have their own income. The purpose of this PKM activity is to broaden students' horizons regarding the goals and benefits of saving from an early age and to foster an interest in saving for students from an early age even though they do not have their own income. The stages of this activity start from preparation, implementation of service activities in the form of socializing fond of saving from an early age and ending with the stage of writing service activity reports. Socialization activities like saving from an early age were followed by all students as participants in this PKM activity enthusiastically so that they were able to increase students' understanding and broaden their horizons regarding the importance of saving from an early age even though they do not have an independent income. Activities like this need to be carried out elsewhere so that the knowledge and interest of students as the younger generation in saving continues to increase so that they can contribute to economic improvement for the nation and state in the future. The expected output of this community service activity focuses on increasing students' understanding of the importance of saving activities and being aware of the importance of saving activities from an early age and can be one of the inputs for the school so that saving activities can become a routine activity for students coordinated by each homeroom teacher